A Simple and Promising Strategy for Pancreatic Islet Preconditioning to Reduce Immunogenicity and Improve Islet Graft Longevity. (July 2018) - Anazawa, Takayuki; Yamane, Kei; Tada, Seiichiro; Inoguchi, Kenta; Sato, Naoya; Masui, Toshihiko; Nagai, Kazuyuki; Sumi, Shoichiro; Okajima, HIdeaki; Uemoto, Shinji
Abstract : Introduction: An advantage of pancreatic islet transplantation is that the pretransplant in vitro culture period provides an opportunity for cell modification; however, no "islet preconditioning" method has been established yet. We previously reported that the pretreatment of donor islets with an antitumoral antibiotic, mitomycin-C (MMC), and subsequent culture significantly prolonged graft survival in murine renal subcapsular islet transplantations. Here, we introduce an "islet preconditioning" strategy for reducing the immunogenicity of islets and for preventing the activation of proinflammatory events by using MMC in an intraportal islet transplantation model. Methods: Freshly isolated BALB/c islets, either untreated or treated for 30 min with 10 μg/mL MMC, were cultured for 20 hours. Subsequently, 600 allogenic islets were transplanted via the portal vein into the liver of C57BL/6N diabetic mice. Recipients did not receive any immunosuppressive treatment. To demonstrate the specific mechanism responsible for prolonging graft survival by islet preconditioning, immunohistochemical studies and inflammatory cytokine assays were conducted. Microarrays were employed to comprehensively analyze the genes expressed in untreated or MMC-treated islets that were subsequently cultured and to identify the biological processes that were most affected by islet preconditioning. Results: On islet transplantation, the allograft was rejected by all control mice (n = 11), with a mean survival time (MST) of 13.0 ± 8.3 days. Islet conditioning with MMC significantly prolonged islet allograft survival to an MST of 41.4 ± 7.3 days (n = 14) (P < 0.005). Notably, 42.8% of the recipients accepted islet allografts pretreated with MMC for more than 60 days without any immunosuppression. As shown by immunohistochemical studies, compared with untreated grafts, MMC-treated grafts showed a mild inflammatory cell response and minimal infiltration of immunocompetent cells. In an in vitro study, the expression of IL-6, MCP-1, ICAM-1, and IL-1β was significantly decreased in MMC-treated islets compared with untreated islets. Microarray gene expression analysis identified a significant downregulation of annotated functions associated with the movement of cells and revealed significant downregulation of multiple genes encoding proinflammatory mediators with chemotactic activity. Validation studies also showed that MMC-treated islets secreted lower levels of chemoattractants that reduced the immunogenic potential of islets. Conclusion: Islet preconditioning with MMC and subsequent culture can prolong graft survival in intraportal islet transplantations by inhibiting the activation of proinflammatory events and by provoking the suppression of chemoattractants that are responsible for inducing unresponsiveness to islet grafts. This simple and promising islet preconditioning method could be an effective strategy inducing a breakthrough in establishing advanced islet transplantation.